Reimagining habitat suitability modeling for Pacific saury (Cololabis saira) in the Northwest Pacific Ocean through acoustic data analysis from fishing vessels - Minghua Xue; Jianfeng Tong; Wen Ma; Zhenhong Zhu; Weiqi Wang; Shuo Lyu; Xinjun Chen (Ecological Informatics)
The Pacific saury (Cololabis saira) in the Northwest Pacific Ocean holds significant economic value. Understanding the relationship between its distribution and habitat is crucial for ecosystem-based fishery management. Acoustic data from fishing vessels provide a new option for describing the relative abundance of Pacific saury. We transformed opportunity acoustic data collected from Pacific saury fishing vessel during the summer fishing season of 2021 into an acoustic index that is suitable for habitat modeling. The acoustic index was used to develop a habitat suitability index (HSI) model. Meanwhile, generalized additive models were applied to select environmental variables for modeling, and boosting regression tree-weighted analyses were employed to determine the weights of these variables. Instead of traditional fishing effort or catch per unit effort (CPUE) based HSI models, this acoustic index-based model offered an innovative approach with immutable evidence for establishing the relationship between sea surface temperature (SST, °C), sea surface temperature gradient (SSTG, °C/°), sea surface height (SSH, m), and chlorophyll a concentration (Chl, mg/m3) with suitable habitats. The validity of the acoustic index in HSI modeling was tested with the catch data. This study showed that SSH had the most important impact on acoustical relative abundance, followed by SST, Chl and SSTG. The suitability index model determined the optimal habitat ranges for the four environmental variables. Cross-validation results indicated that the HSI model developed using the arithmetic mean method can better predict the distribution of suitable habitats than the geometric mean method. The HSI results matched the catch distribution well. This study contributes to further exploration of the marine variables' impact on suitable fish habitats based on acoustic indices and provides scientific references for ecosystem-based fishery management.